The Application of Hydrotherapy (Warm Salt Water Soaking) to Reduce Pain in Patients with Gout Arthritis: A Case Study: Studi Kasus: Penerapan Hidroterapi (Rendam Air Hangat dengan Garam) untuk Menurunkan Nyeri pada Pasien dengan Gout Arthritis - LL.. Herwandi Wiladarma Wandi; Ahyar Rosidi (PT. Sentra Ilmiah Teknologi Mandiri, 2026)
Gout arthritis is an inflammatory joint disease caused by the accumulation of monosodium urate crystals due to elevated uric acid levels in the blood. According to the World Health Organization (WHO) in 2023, the global prevalence of gout arthritis ranges from 5% to 30% and continues to increase, including in Indonesia. This case study aimed to determine the application of hydrotherapy (warm salt water soaking) in reducing pain intensity in a patient with gout arthritis in Pejeruk Hamlet, Pengadangan Village. This study employed a case study design using a nursing care approach on one patient with gout arthritis. The intervention consisted of hydrotherapy (warm salt water soaking) administered for 3 × 24 hours. After the warm salt water soaking intervention was administered for three consecutive days, the patient's pain level decreased, as indicated by reduced pain complaints, increased comfort, and improved ability to perform daily activities. The application of hydrotherapy (warm salt water soaking) was effective in reducing pain intensity in patients with gout arthritis and can be used as a non-pharmacological nursing intervention.